Gut microbiota contributes to sexual dimorphism in murine autoimmune cholangitis. Issue 6 (28th May 2021) - Huang, Meng-Xing; Yang, Si-Yu; Luo, Pan-Yue; Long, Jie; Liu, Qing-Zhi; Wang, Jinjun; He, Yi; Li, Liang; Zhao, Zhi-Bin; Lian, Zhe-Xiong
Abstract: The data demonstrated that a transgenic murine model of primary biliary cholangitis (PBC), expressing dominant negative TGF-β receptor Ⅱ (dnTGFβRⅡ) under the CD4 promoter, showed similarity to PBC patients that is female-dominant. Female dnTGFβRII mice developed more severe lymphocytic infiltration in the liver and had higher levels of inflammatory cytokines, including IFN-γ and TNF-α, than the male mice. Interestingly, elimination of testosterone through gonadectomy in male dnTGFβRII mice did not influence disease severity, supporting that testosterone is an unessential factor in sustaining liver immune homeostasis. Meanwhile, it was observed that treating dnTGFβRII mice with oral antibiotics markedly reduced the differences in the levels of lymphocytic infiltration and cytokines between males and females, suggesting that the commensal gut microbiome plays a role in determining the observed sexual differences in dnTGFβRII mice. Furthermore, the diversity of gut microbiota composition and their metabolic functions in the male and female groups through metagenomic sequencing analysis were identified. The results revealed a testosterone-independent and commensal gut microbiota-mediated female bias in PBC. Graphical Abstract: Testosterone-independent and gut microbiota-mediated sexual differences were identified in a murine model of primary biliary cholangitis.